"Cosmologies in Transition: Continuity and Transformation in the Material Record". Full day session at the 36th Annual Conference of the Theoretical Archaeology Group, TAG 2014, Manchester (United Kingdom), 15th–17th December, 2014. (9th March 2015) - Connolly, David
Abstract : This session, organized by Fabio Silva (University College London and University of Wales Trinity Saint David), was aimed at furthering "our understanding of periods of economical, social, religious or technological transition, their impact on the cosmologies of those involved and how these are imprinted on the archaeological record". It was a serious attempt to broaden the celestial horizons of archaeoastronomy beyond the narrow boundaries assigned it by mainstream archaeology, and ironically, although taking place away from the main conference building, it was well attended with more people arriving as the day continued.